Metformin inhibits pro‐inflammatory responses via targeting nuclear factor‐κB in HaCaT cells. (5th December 2018) - Ba, Wei; Xu, Yuanyuan; Yin, Guang; Yang, Jingrun; Wang, Rui; Chi, Sumin; Wang, Yinyin; Li, Chengxin
Abstract : Psoriasis is a prevalent, chronic inflammatory skin disease that arises from rapid and excessive growth of keratinocytes induced by abnormal inflammatory responses. Metformin is the first‐line drug in type 2 diabetes and has been proven to possess significant anti‐inflammatory effects in various diseases. In the present study, we examined the role of metformin in nuclear factor kappa B (NF‐κB)–mediated inflammatory responses in HaCaT cells, a cell line for the keratinocyte. Our results demonstrated that metformin significantly decreased the mRNA and protein levels of tumour necrosis factor‐α (TNFα), interleukin (IL)‐6, IL‐8, and IL‐1β induced by TNFα. Immunofluorescence staining and western blot analysis showed that metformin inhibited the nuclear localization of p65, a subunit of nuclear factor NF‐κB. In addition, metformin suppressed the transcription activity of NF‐κB by inhibiting the degradation of IκBα. The inhibitory effect of metformin on NF‐κB signalling is comparable with a specific IKKβ inhibitor BI605906. Collectively, our data suggest that metformin may be a potential therapeutic agent in inflammatory skin diseases like psoriasis.